Cryptocurrency adoption and its influence on financial stability in emerging markets - Minarni, Eni (Jurnal Konseling dan Pendidikan, 2025)
This study explores the adoption of cryptocurrency and its influence on financial stability in emerging markets through a qualitative literature review. With the rapid growth of digital currencies, understanding their impact on financial systems has become increasingly crucial, particularly in developing economies where traditional banking infrastructure may be limited. The research synthesizes existing scholarly articles, reports, and case studies to identify key factors influencing l. cryptocurrency adoption, including regulatory frameworks, technological infrastructure, and societal attitudes towards digital currencies. Furthermore, the study examines the potential benefits and risks associated with cryptocurrency adoption, such as increased financial inclusion, volatility, and the challenges of regulatory oversight. By analyzing these dimensions, the research aims to provide a comprehensive understanding of how cryptocurrency can affect financial stability in emerging markets. The findings suggest that while cryptocurrency adoption presents opportunities for enhancing financial access and innovation, it also poses significant risks that could undermine financial stability if not managed effectively. This study contributes to the ongoing discourse on digital currencies by highlighting the need for balanced regulatory approaches that promote innovation while safeguarding financial systems. The insights gained from this research can inform policymakers and stakeholders in emerging markets as they navigate the complexities of integrating cryptocurrencies into their financial ecosystems.